2015
DOI: 10.1002/2014jc010231
|View full text |Cite
|
Sign up to set email alerts
|

Structure of turbulence and sediment stratification in wave‐supported mud layers

Abstract: We present results from laboratory experiments in a wave flume with and without a sediment bed to investigate the turbulent structure and sediment dynamics of wave-supported mud layers. The presence of sediment on the bed significantly alters the structure of the wave boundary layer relative to that observed in the absence of sediment, increasing the TKE by more than a factor of 3 at low wave orbital velocities and suppressing it at the highest velocities. The transition between the low and high-velocity regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 67 publications
11
39
0
Order By: Relevance
“…Sediment concentration profiles at both sites show a high concentration layer with a thickness ranging between 5 and 20 cm and high concentration gradients (Figures g–i). The concentration profiles show an exponential decay with maximum concentrations near the bed (Figures g–i), similar to other field and laboratory experiments (Hooshmand et al, ; Lamb & Parsons, ; Souza et al, ; Traykovski et al, ).…”
Section: Observations and Resultssupporting
confidence: 88%
“…Sediment concentration profiles at both sites show a high concentration layer with a thickness ranging between 5 and 20 cm and high concentration gradients (Figures g–i). The concentration profiles show an exponential decay with maximum concentrations near the bed (Figures g–i), similar to other field and laboratory experiments (Hooshmand et al, ; Lamb & Parsons, ; Souza et al, ; Traykovski et al, ).…”
Section: Observations and Resultssupporting
confidence: 88%
“…We found that the velocity decayed to zero at the bottom boundary, unlike our field measurements in which the velocity decayed to zero at the top of the canopy. These results mirrored those found in a recent laboratory study using a Vectrino in a sediment flume (Hooshmand et al, 2015). This is further evidence that our reported velocity profiles are showing physical flow features rather than measurement errors.…”
Section: Vectrino Error Analysissupporting
confidence: 90%
“…ABS instruments have been calibrated in a similar manner to this study, using a maximum SSC of 33 g L −1 , based on the sound absorption parameters of their specific suspended‐sediment distribution [ Traykovski et al , ]. In flume experiments with a similar grain‐size distribution to this study, observed SSC maxima were 50–70 g L −1 [ Hooshmand et al ., ]. Because SSC exerts a first‐order control on U g in equation , this study imposes a maximum SSC (SSC max ) of 50 g L −1 to prevent artificially over‐predicting the relative importance of WSFM in off‐shelf sediment transport.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, using sensitive instrumentation capable of detecting thin, near‐bed layers in a harsh ocean environment is difficult. To improve our understanding of the controls of WSFM dynamics, several studies have successfully generated high‐density conditions in laboratory flumes [e.g., Lamb and Parson , ; Hooshmand et al ., ] and numerical simulations [e.g., Traykovski et al , ; Ozdemir et al , , ]. These studies accommodate control of the individual WSFM drivers (e.g., U w , SSC, and α ), and allow for detailed observation of their behavior.…”
Section: Introductionmentioning
confidence: 99%